Survivorship for Individuals Living With Advanced and Metastatic Cancers: National Cancer Institute Meeting Report. (8th December 2021) - Mollica, Michelle A; Smith, Ashley Wilder; Tonorezos, Emily; Castro, Kathleen; Filipski, Kelly K; Guida, Jennifer; Perna, Frank; Green, Paige; Jacobsen, Paul B; Mariotto, Angela; Tesauro, Gina; Gallicchio, Lisa
Abstract: An important and often overlooked subpopulation of cancer survivors is individuals who are diagnosed with or progress to advanced or metastatic cancer. Living longer with advanced or metastatic cancer often comes with a cost of burdensome physical and psychosocial symptoms and complex care needs; however, research is limited on this population. Thus, in May 2021, the National Cancer Institute convened subject matter experts, researchers, clinicians, survivors, and advocates for a 2-day virtual meeting. The purpose of this report is to provide a summary of the evidence gaps identified by subject matter experts and attendees and key opportunities identified by the National Cancer Institute in 5 research areas: epidemiology and surveillance, symptom management, psychosocial research, health-care delivery, and health behaviors. Identified gaps and opportunities include the need to develop new strategies to estimate the number of individuals living with advanced and metastatic cancers; understand and address emerging symptom trajectories; improve prognostic understanding and communication between providers, patients, and caregivers; develop and test models of comprehensive survivorship care tailored to these populations; and assess patient and provider preferences for health behavior discussions throughout the survivorship trajectory. To best address the needs of individuals living with advanced and metastatic cancer and to deliver comprehensive evidence-based quality care, research is urgently needed to fill evidence gaps, and it is essential to incorporate the survivor perspective. Developing such an evidence base is critical to inform policy and practice.